Classification of cultivated rice seed of MR219 and MR269 varieties based on colour features using machine vision technique - Ahmad Yusuf Hashim (School of Biosystem Engineering, University Malaysia Perlis, 2016)
This project was focusing on the rice seed sample that acquired from the authorized rice seed distributor. The types of rice seed that been chosen are MR219 and MR269 because it is the most commercially used seed in Malaysia. The project was undergone in CeasTECH lab using machine vision equipment that consist of a black box, CCD camera and light bulb. The study involved in classifying two rice seed varieties of MR219 and MR269. The classification were carried out based on the colour feature of the seed only.